(untitled) (Konferensiyalar | Conferences, 2024)
Language as a social phenomenon requires us to learn it from sociolinguistic point of view for effectively communicating with interlocutors in different situations without any misunderstandings. The best way of enhancing reading comprehension and communication skills in non-linguistic universities is sociolinguistic approach which will be defined based on different scientists’ views in our article.